Strategi Koping Pada Anak yang Memiliki Pengalaman Kehilangan Orang Tua di LKSA Nugraha Kota Bandung - Denny Maulana Pratama (Politeknik Kesejahteraan Sosial Bandung, 2021)
The purpose of this research was to describe and analyze the characteristics of the child, the background of the child's parental loss, problem-centered strategies, and child-centered emotional strategies. This research uses qualitative methods with a descriptive approach. The informants in this study included 6 children and 2 caregivers. The data collection techniques used in this study were in-depth interviews and documentation studies. Data validity checks were also carried out through source and time triangulation. The data analysis technique was carried out through data reduction, data presentation, and concluding. The results showed that the coping strategies carried out by the children were classified as good because they carried out two types of coping, namely strategies focusing on problems and strategies focusing on emotions, but there were still problems with strategies that focused on problems, namely the children did not have the initiative to express problems to caregivers and there was no media available group meeting to reveal the problems of losing parents. Besides, there are also problems in the strategy to focus on emotions, namely that children choose not to express the emotions they feel, there is still a rejection of the loss of their parents, and feelings of inferiority that are still possessed by children who have experiences of losing their parents. Based on these problems, the researchers formulated an empowerment program for groups of children who had experiences of losing their parents.